Carbon as Quasi-Reference Electrode in Unconventional Lithium-Salt Containing Electrolytes for Hybrid Battery/Supercapacitor Devices. Issue 14 (1st January 2016) - Widmaier, M.; Krüner, B.; Jäckel, N.; Aslan, M.; Fleischmann, S.; Engel, C.; Presser, V.
Abstract : Metallic lithium is the most widespread reference electrode in lithium ion battery research, but its high reactivity limits the usage primarily to conventional carbonate based electrolytes. Novel high power concepts, like hybrid supercapacitors, require lithium containing electrolytes with high ionic conductivity (e.g., acetonitrile), which are not always stable versus lithium. In the current work we face this issue by refining activated carbon as a quasi-reference electrode originally employed for conventional supercapacitors. Different commercially available carbon powders were examined as reference electrode materials and calibrated in lithium-salt containing acetonitrile versus Li + intercalation/de-intercalation reaction of nanoparticulate Li4 Ti5 O12 . The stability of the activated carbon reference electrode is highly affected by the salt employed and decreases in the following order: LiTFSI > LiClO4 > LiPF6 > LiBF4 . Only a negligible impact of electrolyte solvent, pore size distribution and reference electrode binder was observed. Furthermore, activated carbon was functionalized (HNO3 treated) and de-functionalized (thermal annealing in vacuum or hydrogen) to investigate the impact of carbon functionalization on the reference electrode stability. Nitrogen and oxygen containing surface groups have been found to drastically improve long-term stability of activated carbon quasi-reference electrodes. Even after 15 days exposed to the electrolyte, the potential of HNO3 treated activated carbon is marginally altered by 10 mV.